The experimental study of TNF-α & CRP expression in the spinal tuberculosis after instrumentation. (December 2021) - Risantoso, Tjuk; Hidayat, Mohammad; Suyuti, Hidayat; Aulann'iam,
Abstract: Introduction: Previously, the management of spinal TB was using drugs and external stabilization. Surgical techniques were developed afterwards to clean the infected vertebral segment. The TB treatment approach is now based on immunology because the bacteria Mycobacterium tuberculosis has unique characteristics and the increasing cases of MDR (multiple drug resistant) TB due to mutation processes. TNF-α and CRP has a major role in immune activity of spinal TB. The energy from metal devices composed of ions and particles that have been used in instrumentation is expected to reduce the biomolecular and biocellular activity of the spinal tuberculosis inflammation activity. This study aims to investigate TNFα and CRP value as evaluator of bone inflammation activity in Spinal TB through experimental studies in Laboratory at Veterinary Faculty, Universitas Brawijaya. Methods: We investigates 40 New Zealand Rabbits which were given TB H37Rv strain infection in the vertebral body. Samples were divided into five groups namely control rabbits, infected rabbits without intervention, infected rabbits treated by instrumentation, infected rabbits given anti-tuberculosis drugs and infected rabbits treated by instrumentation and given drugs. The cytokine levels of TNF-α and CRP were evaluated and compared as the main outcome. Result: The results showed a notable TNF-α and CRP decrease in infected rabbits given drugs alone and instrumentation alone compared to infected rabbits without intervention. There was a significant TNF-α and CRP decrease in infected rabbits given drugs and treated by instrumentation compared to control rabbits and rabbits who received drugs only. Conclusion: Instrumentation can reduce the inflammation activity in spinal tuberculosis by affecting the body's cytokine levels. Highlights: In conclusion, the use of metal/titanium instruments to produce energy emissions through the instrument directly affect the immune activity of bone inflammation. Limitation of this study that this research is still using experimental animals. Further research should explain clearer information about the implant energy resonance activity in diseased tissues.